10Cr1MoW강에서 응고속도에 따른 δ 페라이트 형성거동 - 권순철; Suncheol Kwon; 주윤곤; Yunkon Joo; 성창훈; Changhoon Sung; 손명균; Myunggyun Son; 신종호; Jongho Shin; 서성문; Seongmoon Seo; et al. (대한금속·재료학회지, 56(8), 2018)
Martensitic 10Cr1MoW steels are widely used for high temperature components in turbine engines because they have good mechanical properties and corrosion resistance. Delta-ferrite can form locally in large ingots and the ferrite phase degrades the metal’s high-temperature properties. To decrease the fraction of delta-ferrite the solidification process should be controlled. In this paper, directional solidification experiments were carried out with martensitic 10Cr1MoW steel at various growth velocities, 5 μm/s - 50 μm/s. The fraction and size of the delta ferrite declined with increasing growth velocity, and also declined with increasing distance from the solid/liquid interface of the directionally solidified sample. These results are discussed in relation to the dendrite spacing of the delta primary phase, and precipitation of the gamma phase with solidification rates. As the solidification velocity decreased and the distance from the solid/liquid interface increased, the fraction of delta ferrite increased. (Received May 9, 2018; Accepted June 14, 2018)